The Intracellular and Extracellular Microenvironment of Tumor Site: The Trigger of Stimuli‐Responsive Drug Delivery Systems. Issue 3 (20th January 2022) - Jing, Xiaodong; Hu, Hao; Sun, Yanzhen; Yu, Bing; Cong, Hailin; Shen, Youqing
Abstract: The tumor microenvironment (TME), including intracellular and extracellular microenvironment, contains many biochemical indicators (such as acidity/alkalinity, oxygen content, and enzymatic activity) that are different from the normal physiological environment. These abnormal biochemical indicators can accelerate the heterogeneity of tumors, but on the other hand, they also provide opportunities for the design of intelligent drug delivery systems (DDSs). The TME‐responsive DDSs have shown great potential in reducing the side effects of chemotherapy and improving the curative effect of tumors. In this review, the abnormal biochemical indicators of TME are introduced in detail from both the extracellular and intracellular aspects. In view of the various physiological barriers encountered during drug delivery, the strategy of constructing TME‐responsive DDSs is discussed. By summarizing the typical research progress, the authors prospect the development of TME‐responsive DDS in the future. Abstract : In this review, the abnormal biochemical indicators of the tumor microenvironment (TME) are introduced in detail from both the extracellular and intracellular aspects. In view of the various physiological barriers encountered during drug delivery, the strategy of constructing TME‐responsive drug delivery systems (DDSs) is discussed. Finally, the authors prospect the development of TME‐responsive DDSs by summarizing the typical research progress.